(untitled) (Analysis in Theory and Applications, 2022)
In this work we consider the following class of elliptic problems cases −∆_Au + u = a(x)|u|^q−2u + b(x)|u|^p−2u & in & R^N, u ∈ H^1_A (R^N), P cases with 2 < q < p < 2^∗ = 2NN−2, a(x) and b(x) are functions that can change sign and satisfy some additional conditions; u H^1_A (R^N) and A : R^N → R^N is a magnetic potential. Also using the Nehari method in combination with other complementary arguments, we discuss the existence of infinitely many solutions to the problem in question, varying the assumptions about the weight functions.